Adopting Full Dollarization in Postconflict Economies : Would the Gains Compensate for the Losses in Liberia? - Schumacher, Liliana (IMF Working Papers; Working Paper ;, 2006)
This paper discusses whether adopting the U.S. dollar as the sole legal tender could help Liberia, a postconflict economy, to boost growth and strengthen fiscal discipline. In view of the performance of exchange rate regimes in many countries and Liberia's own experience with dollarization, we conclude that Liberia should not adopt full dollarization for the following reasons: (i) the alleged benefits voiced by the proponents of dollarization, in terms of enhanced fiscal discipline and faster economic growth, are not supported by the empirical evidence; (ii) dollarization would increase the Liberian economy's vulnerability to external shocks and Liberia's social fragility; (iii) banks in fully dollarized economies face additional capitalization requirements that Liberian banks cannot meet at present; and (iv) dollarization would be costly in terms of real resources because of the loss of seigniorage.